Enhanced surveillance of syphilis cases among men who have sex with men in London, October 2016–January 2017. (April 2019) - Rana, Sangeeta; Macdonald, Neil; French, Patrick; Jarman, Jay; Patel, Sheel; Portman, Mags; Suchak, Tara; Sullivan, Ann; White, John; Crook, Paul
Syphilis rates have been increasing in men who have sex with men (MSM) in London. To describe risk behaviour and refine public health interventions, we conducted prospective enhanced surveillance of new syphilis cases in MSM attending selected London sexual health clinics (SHCs) between October 2016 and January 2017. Sexual health advisors (SHAs) completed 107 questionnaires. Eighteen per cent of respondents reported always using condoms, with lower use in HIV-positive (8%, 4/53) than HIV-negative men (33%, 14/52). Almost half of respondents reported condomless sero-discordant sex (46%, 33/72). The most frequent means of meeting new partners reported were venues (80%, 76/95), particularly bars or clubs (34%, 32/95), and apps or websites (79%, 75/95). Nearly a third of respondents reported engaging in group sex (32%, 30/95). Almost half reported drug use during sex (47%, 46/98), with HIV-positive men more likely to report use of the three main 'chemsex' drugs. The majority of respondents preferred health promotion information from SHAs (63%, 58/92) compared to other sources such as Google/Wikipedia and apps. Prevention activity should continue to focus on condomless sex, serosorting, multiple and overlapping partners, and chemsex. SHCs, particularly those serving HIV-positive men, are important sources for sexual health promotion advice.